2018
DOI: 10.1111/ijfs.13997
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological, chemical and sensory aspects of bread supplemented with different percentages of the culinary mushroom Pleurotus eryngii in powder form

Abstract: Pleurotus eryngii (DC.) Qu el. powder was used in bread production. Three dough trials (0, 5 and 10% of mushroom) were obtained with commercial baker's yeast. P. eryngii powder was first tested against several yeast species; 10% P. eryngii trial was characterised by the highest pH and total titratable acidity. P. eryngii did not influence negatively the fermentation process, since all trials reached yeast levels of 10 8 CFU g À1 . Mushroom powder decreased bread height and softness, increased crust redness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
4
28
0
1
Order By: Relevance
“…According to Olawuyi and Lee (), the replacement of rice flour by shiitake mushroom powder (5%–10%) in muffins resulted in better consumer acceptability values compared to rice muffin, but samples were also sensory evaluated by Asian people. However, when an Italian panel tested an addition of 5%–10% of Pleurotus eryngii powder to wheat flour to produce bread, odor was worse evaluated compared to control bread (Gaglio et al, ). In the current work, the burgers with 2.5% flour, which presented flavor and taste scores of around 3, could be an acceptable option to introduce the taste to the consumers, while providing a reduction of fat and salt.…”
Section: Resultsmentioning
confidence: 99%
“…According to Olawuyi and Lee (), the replacement of rice flour by shiitake mushroom powder (5%–10%) in muffins resulted in better consumer acceptability values compared to rice muffin, but samples were also sensory evaluated by Asian people. However, when an Italian panel tested an addition of 5%–10% of Pleurotus eryngii powder to wheat flour to produce bread, odor was worse evaluated compared to control bread (Gaglio et al, ). In the current work, the burgers with 2.5% flour, which presented flavor and taste scores of around 3, could be an acceptable option to introduce the taste to the consumers, while providing a reduction of fat and salt.…”
Section: Resultsmentioning
confidence: 99%
“…A few researchers have previously examined the impact of incorporating mushroom flours into breads and cookies on their physicochemical and sensory properties (Jung & Joo, 2010;Lee & Jeong, 2009;Raimondo et al, 2018;Ulziijargal, Yang, Lin, Chen, & Mau, 2013;Yuan, Zhao, Yang, et al, 2017). These studies all suggested that mushroom flour could be successfully incorporated into baked goods without adversely affecting their preparation and final properties, provided too much was not added.…”
mentioning
confidence: 99%
“…Indeed, consumers are more and more aware of food composition and are demanding foods with no chemical preservatives [28] that are able to prevent health problems or diseases [29]. Several recent studies focused on fermentation by commercial baker's yeast to produce fortified bread with dietary fibers, vitamins, and antioxidants [11,22,30]. Furthermore, these studies have investigated the microbiological and physicochemical parameters of fortified bread with legumes, fungi, and vegetative part of plants, but very little is known about bread fortification with edible nuts, such as pistachio, in order to produce lysine-enriched breads.…”
Section: Discussionmentioning
confidence: 99%
“…Each dough of 406 g was produced following the protocol reported by Gaglio et al [11] with a dough yield (weight of the dough/weight of the flour × 100) of 160. Briefly, control doughs (CF and CS) were obtained from 246 g of wheat flour or semolina, 150 mL of tap water, 4 g of baker's yeast and 6 g of NaCl while experimental doughs (EFP and ESP) were obtained with the same amount of tap water, baker's yeast and NaCl added to 233.7 g of wheat flour or semolina and 12.3 g (5% of wheat flour/semolina weight) of pistachio powder.…”
Section: Raw Materials and Dough Productionmentioning
confidence: 99%
See 1 more Smart Citation